The N-acetyltransferase 10 inhibitor [11C]remodelin: synthesis and preliminary positron emission tomography study in mice - Rui Luo; Yiding Zhang; Katsushi Kumata; Lin Xie; Yusuke Kurihara; Masanao Ogawa; Tomomi Kokufuta; Nobuki Nengaki; Feng Wang; Ming-Rong R. Zhang (EJNMMI Radiopharmacy and Chemistry)
Abstract Background 4-(4-Cyanophenyl)-2-(2-cyclopentylidenehydrazinyl)thiazole (remodelin) is a potent N-acetyltransferase 10 (NAT10) inhibitor. This compound inhibits tumors and weakens tumor resistance to antitumor drugs. Moreover, remodelin has been found to enhance healthspan in an animal model of the human accelerated ageing syndrome. In this study, we synthesized C-11-labelled remodelin ([11C]remodelin) for the first time as a positron emission tomography (PET) probe and assessed its biodistribution in mice using PET. Results [11C]Remodelin was synthesized by the reaction of a boron ester precursor (1) with hydrogen [11C]cyanide, which was prepared from the cyclotron-produced [11C]carbon dioxide via [11C]methane. The decay-corrected radiochemical yield of [11C]remodelin was 6.2 ± 2.3% (n = 20, based on [11C]carbon dioxide) with a synthesis time of 45 min and radiochemical purity of > 90%. A PET study with [11C]remodelin showed high uptake of radioactivity in the heart, liver, and small intestine of mice. The metabolite analysis indicated moderate metabolism of [11C]remodelin in the heart. Conclusions In the present study, we successfully synthesized [11C]remodelin and assessed its biodistribution of radioactivity in the mouse organs and tissues with PET. We are planning to prepare tumor and inflammatory models in which overexpression of NAT10 is possibly induced and conduct PET imaging for these animal models with [11C]remodelin to elucidate the relationship between NAT10 and diseases.